Chikungunya Virus as Cause of Febrile Illness Outbreak, Chiapas, Mexico, 2014 - Kautz, Tiffany F.; Díaz González, Esteban Eduardo; Erasmus, Jesse H.; Malo García, Iliana Rosalía; Langsjoen, Rose M.; Patterson, Edward I.; Auguste, Dawn I.; Forrester, Naomi L.; Sánchez Casas, Rosa María; Hernández Ávila, Mauricio; Alpuche Aranda, Celia M.; Weaver, Scott C.; et al. (National Center for Infectious Diseases, Centers for Disease Control and Prevention (CDC), 2015)
Since chikungunya virus (CHIKV) was introduced into the Americas in 2013, its geographic distribution has rapidly expanded. Of 119 serum samples collected in 2014 from febrile patients in southern Mexico, 79% were positive for CHIKV or IgM against CHIKV. Sequencing results confirmed CHIKV strains closely related to Caribbean isolates.